Uwięziony mason, Natan mędrzec i Inkowie, czyli rzecz o sztuce pewnego niemieckiego barona w kontekście oświeceniowej idei tolerancji - Śrama, Marcin (Studia Europaea Gnesnensia, 2019)
This paper discusses the drama entitled “Le franc-maçon prisonnier”, whose French-language version written by Hans Heinrich Freiherr von Ecker und Eckhoffen was published in 1777, (the longer German version, i.e. Der Freymaurer im Gefängnis, signed Hans Karl Freiherr von Ecker und Eckhoffen followed a year later), in the context of the Enlightenment concept of tolerance, and the Freemasonic and literary activity of the brothers (co-authors, or the author and the translator of the work). The issues relating to the piece and the literary work of the von Ecker und Eckhoffens has not been previously addressed in any publications in Polish.